Kwanghae wang i toen namja - Ch'u, Ch'ang-min; Hwang, Cho-yun; Yi, Pyŏng-hŏn; Ryoo, Seung-yong; Han, Hyo-ju
Joseon Dynasty, Korea. It's unsettled times and the unpopular King Gwang-hae knows it. Paranoid others are plotting against him he is poisoned and taken gravely ill. In a remote location he hopes to convalesce. Now vulnerable he needs to deter further assassination attempts. In the meantime a comic, who satirises the royals, is hired as a surrogate to impersonate the king during his period of recovery. In collaboration with the chief advisor the pair must fool the members of the court until the real king can regain his health. It's not long, however, that the surrogate discovers the inequality and rampant corruption inherent in the ruling elite and commences to instigate some changes of his own